Can the Unconscious Mind be Persuaded? An Overview with Marketing Implications - Wongtada, Nittaya (International Review of Management and Marketing, 2018)
Communicating directly with consumer’s unconscious thought is believed to enhance the effectiveness of marketing strategy. The current application of neuroscience in social science studies including marketing reinvigorates the interest in this topic. Thus, this article serves as an overview of the development of knowledge of unconscious communication and persuasion. Although there are some evidences to support the ability to communicate directly with unconscious thoughts and possibility to manipulate the processing of information by the unconscious mind by using subliminal cues, the reliability and validity of these findings are questionable. Inherited weaknesses in neuroscience tools, inappropriate research methodology, and alternative explanations of causal relations are among some threats to the value of current findings. Implications for marketing managers and academic researchers in this uncertain situation are also provided. Keywords: Unconscious thought, neuroscience, marketing JEL Classifications: M31, D87